Effects of vitamin E and C supplementation either alone or in combination on exercise-induced lipid peroxidation in trained cyclists - Bryant, R. J.; Ryder, J.; Martino, P.; Kim, J.; Craig, (The Journal of Strength and Conditioning Research, 2003)
Seven trained male cyclists (age 22.3 ± 2 years) participated in 4 separate supplementation phases. They ingested 2 capsules per day containing the following treatments: placebo (placebo plus placebo); vitamin C (1 g per day vitamin C plus placebo); vitamin C and E (1 g per day vitamin C plus 200 IU per kg vitamin E); and vitamin E (400 IU per kg vitamin E plus placebo). The treatment order (placebo, vitamin C, vitamin C and E, and vitamin E) was the same for all subjects. Performance trials consisting of a 60-minute steady state ride (SSR) and a 30-minute performance ride (PR) on Cybex 100 Metabolic cycles were performed after each trial. Workloads of 70% of the O2max were set for the SSR and PR rides, with pedal rate maintained at 90 rpm (SSR) or self determined (PR). Blood samples (5 ml) were drawn pre- and postexercise and analyzed for malonaldehyde (MDA) and lactic acid. The results indicate that vitamin E treatment was more effective than vitamin C alone or vitamin C and E. Pre-exercise plasma levels of MDA in the vitamin E trial was 39% below the pre-exercise MDA levels of the placebo: 2.94 ± 0.54 and 4.81 ± 0.65 mol per ml, respectively. Plasma MDA following exercise in the vitamin E group was also lower than the placebo: 4.32 ± 0.37 vs. 7.89 ± 1.0 mol per ml, respectively. Vitamin C supplementation, on the other hand, elevated both the resting and exercise plasma levels of MDA. None of the supplemental phases had any significant effect on performance. In conclusion, the results indicate that 400 IU/day of vitamin E reduces membrane damage more effectively than vitamin C but does not enhance performance. Athletes are encouraged to include antioxidants, such as vitamin E and C, in their diet to counteract these detrimental effects of exercise. The data presented here suggests that 400 IU/day of vitamin E will provide adequate protection but supplementing the diet with 1 g per day of Vitamin C may promote cellular damage. However neither of these vitamins, either alone or in combination, will enhance exercise performance.